2023
DOI: 10.3390/ijerph20085489
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Inequalities in the Double Burden of Malnutrition among under-Five Children: Evidence from 10 Selected Sub-Saharan African Countries

Abstract: Background: Africa is unlikely to end hunger and all forms of malnutrition by 2030 due to public health problems such as the double burden of malnutrition (DBM). Thus, the aim of this study is to determine the prevalence of DBM and degree of socio-economic inequality in double burden of malnutrition among children under 5 years in sub-Saharan Africa. Methods: This study used multi-country data collected by the Demographic and Health Surveys (DHS) Program. Data for this analysis were drawn from the DHS women’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Studies investigating the risk factors for DBM in individuals have identified associations with a number of factors. These include infant feeding practices, both affluence and poverty (Alaba et al, 2023), advanced maternal age, abdominal obesity in women and larger household sizes (Sunuwar et al, 2020). The interplay between nutritional deprivation and early-life infections contributes to metabolic changes, which we discuss in more detail later in this review, increasing susceptibility to obesity in adulthood (Leocádio et al, 2021).…”
Section: Risk Factors For the Double Burden Of Malnutrition In Ind Iv...mentioning
confidence: 99%
“…Studies investigating the risk factors for DBM in individuals have identified associations with a number of factors. These include infant feeding practices, both affluence and poverty (Alaba et al, 2023), advanced maternal age, abdominal obesity in women and larger household sizes (Sunuwar et al, 2020). The interplay between nutritional deprivation and early-life infections contributes to metabolic changes, which we discuss in more detail later in this review, increasing susceptibility to obesity in adulthood (Leocádio et al, 2021).…”
Section: Risk Factors For the Double Burden Of Malnutrition In Ind Iv...mentioning
confidence: 99%
“…Inadequate access to healthcare services, poor preventative measures and late diagnosis and treatment options significantly contribute to the high mortality rate from CVDs [ 62 – 64 ]. Socioeconomic disparities, including poverty, unemployment and restricted access to good food and physical activity, contribute to the escalating prevalence of CVD risk factors in Africa [ 65 67 ]. Furthermore, the lack of public awareness about CVDs and their risk factors hampers early diagnosis and intervention, leading to complications and increased mortality [ 68 , 69 ].…”
Section: Search Strategymentioning
confidence: 99%
“…Malnutrition is a significant global public health burden, particularly for under‐fives. It is also a barrier to worldwide poverty eradication, productivity and economic expansion (Alaba et al, 2023 ). Undernutrition is a leading cause of morbidity and mortality in children, particularly in tropical regions where children frequently suffer from a combination of pre‐natal and post‐natal malnutrition (Makori et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%